Coordination or conflict? The causes and consequences of institutional overlap in a disaggregated world order - Benjamin Faude; Julia Fuß (Global Constitutionalism, 2020)
Institutional overlap emerges not only as an unintended by-product of purposive state action but also as its deliberate result. In two ways, this article expands existing research on the causes and consequences of institutional overlap. First, we establish that three different types of dissatisfaction may lead states to deliberately create institutional overlap: dissatisfaction with substantive norms and rules, dissatisfaction with decision-making rules and dissatisfaction with the institutional fit of an existing governance arrangement for a given cooperation problem. Each type of dissatisfaction triggers a distinct motivation for the creation of institutional overlap: to induce policy change, to increase influence on collective decision-making or to enhance governance effectiveness. Second, we demonstrate that whereas the motivation to induce policy change leads to interface conflicts, the motivations to increase influence on collective decision-making and to enhance governance effectiveness give rise to inter-institutional coordination. Three empirical case studies on global energy governance, the governance of global development banking and global environmental governance probe these analytical claims.
Keywords: 330; coordination; fragmentation; global legal pluralism; institutional overlap; regime complexes